Suasana Toko, Promosi dan Keputusan Pembelian Konsumen Batik di Garut - Wufron Wufron (Fakultas Ekonomi Universitas Garut, 2018)
This study aims to determine how the shop atmosphere, promotions and purchasing decisions. As well as the influence of Store Atmosphere on Purchasing decisions and the influence of Promotion on Purchasing Decisions. The method used in this is descriptive and causal methods, where the descriptive method is to use the conditions and responses of consumers about Shop Atmosphere, Promotion and Purchase Decisions, while the causal method reveals problems that are a cause-and-effect relationship between two or more variables by using statistics and testing. the truth of previous research is the same as the Store Atmosphere variable, Promotion of Purchasing Decisions. The number of respondents in this study were 108 people with purposive sampling technique with the data analysis method used, namely Multiple Regression, Correlation Coefficient Analysis using the help of IBM SPSS statistic 20. Based on the results of the study, the overall response of respondents about Store Atmosphere, Promotion. and Purchase Decision, said to be quite good, meaning that Rasya batik garutan has not implemented a shop atmosphere, good promotion. Meanwhile, based on hypothesis testing carried out by testing it can be concluded that significantly the Shop Atmosphere, Promotion does not affect the Purchase Decision at the Rasya Batik Garutan Company.